1999
DOI: 10.2307/3666182
|View full text |Cite
|
Sign up to set email alerts
|

Does the Composition of the Compensation Committee Influence CEO Compensation Practices?

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
126
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(134 citation statements)
references
References 17 publications
4
126
2
2
Order By: Relevance
“…The quality of compensation committees directly affects executive compensation through the definition of remuneration packages whose aim is to align manager and shareholder interests. Indeed, scholars highlight that high quality compensation committee leads to better designed executive remuneration contracts that motivate managers to take value-maximizing decisions, resulting in higher firm performance (Newman & Mozes, 1999;Anderson & Bizjak, 2003;Vafeas, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of compensation committees directly affects executive compensation through the definition of remuneration packages whose aim is to align manager and shareholder interests. Indeed, scholars highlight that high quality compensation committee leads to better designed executive remuneration contracts that motivate managers to take value-maximizing decisions, resulting in higher firm performance (Newman & Mozes, 1999;Anderson & Bizjak, 2003;Vafeas, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, we assess whether and how the composition of compensation committee influences the effectiveness of SOPs in aligning managerial interests to those of outside shareholders. Furthermore, we introduce a measure of compensation committee quality, which is broader than the deeply investigated independence of its members (Daily, Johnson, Ellstrand, & Dalton, 1998;Conyon & Peck, 1998;Newman & Mozes, 1999;Vafeas, 2003;Conyon & He, 2004;Conyon, 2014). Finally, we identify the elements of the SOPs that define effective executive remuneration contracts, thus providing also useful contributions to practitioners and regulators.…”
Section: Introductionmentioning
confidence: 99%
“…This led to the recent regulatory and policy reforms. 4 However, this position does not necessarily imply an association between affiliated or interdependent RC members and CEO compensation [11,15]. One possible reason for this is that affiliated or interdependent directors serving on a powerful committee are mindful of their duty to shareholders, regardless of their level of dependence [11].…”
Section: H1: Top Executive Compensation Levels Will Be Relatively Higmentioning
confidence: 99%
“…Therefore, the level of board independence plays a major role in the effectiveness of executive compensation in regard to reducing the agency problem (e.g. [11,[13][14][15][16][17]) and positively relates to constraints on managerial influence [18]. 2 For example, [5].…”
Section: Prior Studies and Hypothesis Developmentmentioning
confidence: 99%
“…Dalton, Daily, Ellstrand, and Johnson, 1998;Daily, Johnson, Ellstrand and Dalton, 1998). Conyon and Peck (1998), Daily et al (1998) andNewman andMozes (1999) have demonstrated that compensation committee composition is important in determining CEO pay. Despite these important social explanations for understanding CEO pay outcomes, there has been hardly any prior research on the "pervasive influence of compensation consultants" (Finkelstein and Hambrick, 1996, page 275).…”
Section: Compensation Consultantsmentioning
confidence: 99%